Intention to Seek Medical Consultation for Symptoms of Upper Respiratory Tract Infection– A Cross-Sectional Survey - CE, Tan; AH, Mohd Roozi; WHR, Wong; SAH, Sabaruddin; NI, Ghani; Z, Che Man (IIUM Medical Journal Malaysia, 2015)
Introduction: The common cold is the commonest reason for primary care encounters worldwide. This paper aims to describe the reasons that influence patients to seek medical consultation for the common cold. Methods: This was a cross-sectional survey conducted among adult patients of an urban teaching primary care clinic. An adapted bilingual survey form was administered by the researchers to obtain data regarding their decision to seek medical consultation for a cold and the reasons for their decision. Quantitative analyses were done to describe the close-ended responses. Open-ended responses were analysed using a qualitative approach and the frequencies of the themes were reported. Results: A total of 320 respondents participated in this study, with a response rate of 91.4%. They were predominantly females (59.4%), Malay (70.9%), and had tertiary education (65.9%). More than half of the patients (52.5%) said they would seek consultation for cold symptoms. Fever was the commonest symptom (57-61%) which compelled them to seek consultation. The commonest reason for seeking consultation was to get medications (41.7%), whereas the commonest reason not to seek consultation was the practice of self-medication (44.2%). Ethnicity was found to be significantly associated with the decision to seek doctor’s consultation. Conclusion: Colds are usually self-limiting and do not result in complications. Empowering patients by providing appropriate self-care knowledge can help to reduce the burden of primary care services. Patients should be taught about red flag symptoms as well as drug safety for medications commonly taken for colds.